P077 Managing an outbreak of infectious syphilis among university students. (30th June 2016) - Bell, Gill; Keegan, Helen; Howlett, Sally
Abstract : Background/introduction: In November 2015 we were surprised by 5 cases of infectious syphilis among university students, including two bisexual males and one female. Mindful of the potential for onward transmission bridging both homosexual and heterosexual networks in this atypical group, we alerted Public Health to a potential outbreak. Aim(s)/objectives: To report on management of an outbreak. Methods: A pre-existing Outbreak Control Team (OCT) liaised by telephone to discuss preliminary control strategies. Student Health services were alerted immediately by telephone and email. Partner notification (PN) for syphilis cases was prioritised and intensified: additional information was collected (descriptions, where/how met, where studying); provider referral was encouraged, and home visits undertaken to reach contacts before the Christmas vacation. Targeted screening and on-line health promotion via student bulletins and social network sites was introduced. Results: From November 2015 – January 2016, a linked network of 37 individuals was identified, of whom 29 (78%) attended. Most contacts attended following provider referral (25/29; 86%). Repeated efforts were required to secure the attendance of several contacts. In all, 7 student cases of infectious syphilis were identified (1 female; 2 heterosexual males, 2 bisexual males, 2 MSM). The last 2 cases, identified in January, had initially tested negative 2–3 weeks after exposure. Conclusion: A swift response, using a range of case finding and health promotion strategies successfully curtailed a nascent outbreak of infectious syphilis among university students. An intensive approach to PN, with an emphasis on provider referral, ensured the majority of partners attended with minimal delay.